Changes in Salt Composition of Soils under Irrigation with Brackish Water in the Steppe Crimea - Klimenko, O. E.; Yevtushenko, A. P.; Klimenko, N. I. (Eurasian soil science, 2022)
The influence of brackish artesian waters used for drip irrigation of gardens in the Sivash area of Crimea on the composition of salts and exchangeable cations of two soils located at different distances from Lake Sivash has been studied. Observations of the dynamics of mineralization and salt composition of irrigation water during three years (2019–2021) indicate that this water is neutral (pH 6.88–7.43) and slightly to moderately saline (1.5–3.4 g/L) with variable chemical composition of soluble salts: calcium chloride—sodium sulfate–chloride—calcium sulfate. Water salinity increases with time and towards Lake Sivash. The high contents of chlorides (15–25 meq/L), sulfates (6–31 meq/L), and Ca 2+ (14–26 meq/L) and a stable and relatively low concentration of (3 meq/L) are characteristic of the irrigation water. Local moistening of soils during drip irrigation has favored local slight sulfate–chloride and chloride magnesium–sodium salinization in a layer of 0–60 cm, which is toxic for fruit crops. The total salt content in the soil has a pulsating regime: it increases in the fall after the irrigation season and decreases in the spring due to salt leaching by atmospheric precipitation deep into the profile and to the sides from tree rows. Slightly brackish water of this salt composition with a salinity of 1.5–2.7 g/L and SAR 2–4 has led to solonetzization of Haplic Kastanozem with an increase in the content of exchangeable Na + up to 6–8% of the sum of exchangeable cations. Irrigation water with salinity above 3 g/L and SAR 3–7 increases the content of exchangeable Na + up to 9–10% of the sum of exchangeable cations in a slightly solonetzic Luvic Kastanozem. Under conditions of progressive salinization of irrigation water and soils, it is necessary to continue monitoring of the salt composition and ion exchange processes in irrigated soils.